INFLUENCE OF TORASEMIDE ON ELECTRICAL INSTABILITY OF THE HEART IN PATIENTS WITH ISCHEMIC MITRAL REGURGITATION POST MYOCARDIAL INFARCTION - I. B. Ibragimova; U. A. Islamova; R. M. Gafurova; A. A. Abdullaev (Российский кардиологический журнал)
Aim. To assess the efficacy of torasemide for changes of electrical instability of the heart in patients with ischemic mitral regurgitation during the period after myocardial infarction. Material and methods. Ninety six patients with mitral regurgitation, with Q-myocardial infarction (Q-MI) had been randomized to two groups. During six months after discharge, in the control group 1, of 46 patients, the standard therapy applied (clopidogrel, acetylsalicylic acid, nebivolol, perindopril). In the study group 2, of 50 patients, additionally torasemide was used. At baseline, in 3 and 6 months Holter ECG monitoring was performed.Results. In the group 1 patients with mitral regurgitation post Q-MI, with the standard treatment, there was decrease of silent myocardial ischemia (3,6±0,5 — baseline; 3,3±0,5 and 3,1±0,3 — in 3 and 6 months, respectively, p<0,05). They showed decrease of the duration of silent and anginal ischemia, depression of ST segment >1 mm, number of patients with supra- and ventricular extrasystoles (p>0,05) and increase of the number of anginal ischemia (2,1±0,4 — baseline, 2,2±0,2 and 2,3±0,1 — in 3 and 6 months, respectively, p>0,05). In the group 2 patients, in 6 months of treatment there was decrease of number of silent (2,1±0,3) ischemia episodes, duration of anginal (7,3±2,1 min) and silent (4,3±1,2 min) ischemia comparing to baseline (8,8±1,2; 10,6±2,7 and 8,8±1,2 min — respectively, p<0,05). Also, they showed decrease of ST depression >1 mm episodes (1,2±0,2 vs 2,0±0,4 mm at baseline) and relative values of the patients number with the registered supra- and ventricular extrasystoles (38% and 44%, respectively, versus 62% and 84% at baseline, p>0,05).Conclusion. The usage of torasemide combination with standard treatment decreases the number of episodes, duration of silent and anginal myocardial ischemia, rate of registered supra- and ventricular extrasystoles in mitral regurgitation patients post Q-MI, comparing to separate standard treatment. Also, the rate of anginal ischemia episodes does not change in 3 and 6 months of standard treatment.